Remote sensing of night lights: A review and an outlook for the future - Levin, Noam; Kyba, Christopher C.M.; Zhang, Qingling; Sánchez de Miguel, Alejandro; Román, Miguel O.; Li, Xi; Portnov, Boris A.; Molthan, Andrew L.; Jechow, Andreas; Miller, Steven D.; Wang, Zhuosen; Shrestha, Ranjay M.; et al. (Remote sensing of environment, 2020)
Remote sensing of night light emissions in the visible band offers a unique opportunity to directly observe human activity from space. This has allowed a host of applications including mapping urban areas, estimating population and GDP, monitoring disasters and conflicts. More recently, remotely sensed night lights data have found use in understanding the environmental impacts of light emissions (light pollution), including their impacts on human health. In this review, we outline the historical development of night-time optical sensors up to the current state of the art sensors, highlight various applications of night light data, discuss the special challenges associated with remote sensing of night lights with a focus on the limitations of current sensors, and provide an outlook for the future of remote sensing of night lights. While the paper mainly focuses on space borne remote sensing, ground based sensing of night-time brightness for studies on astronomical and ecological light pollution, as well as for calibration and validation of space borne data, are also discussed. Although the development of night light sensors lags behind day-time sensors, we demonstrate that the field is in a stage of rapid development. The worldwide transition to LED lights poses a particular challenge for remote sensing of night lights, and strongly highlights the need for a new generation of space borne night lights instruments. This work shows that future sensors are needed to monitor temporal changes during the night (for example from a geostationary platform or constellation of satellites), and to better understand the angular patterns of light emission (roughly analogous to the BRDF in daylight sensing). Perhaps most importantly, we make the case that higher spatial resolution and multispectral sensors covering the range from blue to NIR are needed to more effectively identify lighting technologies, map urban functions, and monitor energy use. •Remote sensing of night lights allows observation of human activity from space.•We provide a historical overview of the development of such night-time sensors.•We highlight various applications of remote sensing of night lights.•We discuss the special challenges associated with remote sensing of night lights.•We provide an outlook for the future of remote sensing of night lights.